Intellectual capital efficiency, technological innovation and family management. Issue 2 (3rd April 2017) - Manzaneque, Montserrat; Ramírez, Yolanda; Diéguez-Soto, Julio
Abstract: Understanding the relation between intellectual capital and innovation has become one of the most relevant topics for both academics and practicing managers in the field of innovation management. This paper attempts to advance this theme by empirically investigating the role played by both human and structural capital efficiency as determinants of achieving technological innovation outputs. This study also examines the moderating role of family management on these relationships. In this paper, we use a matched-pairs design and a conditional logistic regression approach to analyse a sample of 5, 304 Spanish firms for the period 2000–2013. The results show that both the attracting and recruiting of competent human resources and the ability to develop mechanisms to capture and translate knowledge, expertise, and skills of organisational members and stakeholders are important to achieve technological innovation outputs. Our findings also suggest that family management increases the efficiency of human and structural capital to obtain technological innovation outcomes.